PROFIL DOPPLER KAROTIS DAN DOPPLER TRANSKRANIAL PADA PASIEN PRA CORONARY ARTERY BYPASS GRAFT CABG - Erlinawati, Salim Harris (NEURONA, 2014)
INTRODUCTION ATHEROSCLEROSIS IS A SYSTEMIC DISEASE INVOLVING THE INTIMA OF LARGE AND MEDIUM SIZE ARTERIES INCLUDING THE AORTA CAROTID CORONARY AND PERIPHERAL ARTERIES CAROTID INTIMAMEDIA THICKNESS IS A NONINVASIVE MEASURE OF ATHEROSCLEROSIS AND ASSOCIATED WITH FUTURE STROKE RISK STROKE REMAINS A MAJOR CAUSE OF MORBIDITY AND MORTALITY AFTER CORONARY ARTERY BYPASS GRAFT CABG ONE OF THE MOST COMMON OPERATIVE PROCEDURE PERFORMED AROUND THE WORLD